Soluble Urokinase Plasminogen Activator Receptor Is Associated With Subclinical Myocardial Impairment by Speckle Tracking Echocardiography in Lung Cancer Patients - Manshad, Ahmad S.; Ballout, Fatima A.; Borgia, Jeffrey A.; Reiser, Jochen; Okwuosa, Tochukwu M. (Frontiers in Cardiovascular Medicine, 2022)
Background Plasma cardiac biomarkers have emerged as a cost-effective diagnostic tool aimed at early identification of cardiotoxicity. Soluble urokinase plasminogen activator receptor (suPAR) is a bone marrow cell derived signaling molecule that is associated with cardiovascular disease outcomes. Objectives We investigated associations between suPAR and global longitudinal strain (GLS) as a marker of early myocardial impairment in lung cancer patients. Methods We retrospectively analyzed 52 patients with stage IV non-small cell lung cancer with normal left ventricular ejection fraction (LVEF >55%) and without known heart disease or end-stage renal disease (ESRD). We studied associations between cardiac biomarkers and echocardiographic measures of systolic and diastolic function. GLS was analyzed using 2D speckle-tracking echocardiography via vendor-independent software (TomTec). Results Median plasma suPAR was 7.0 ng/mL (interquartile range: 5.4–9.0). Mean LVEF was 61.9 ± 8.3% and mean GLS was-19.3 ± 2.1%. Inter-observer reproducibility was excellent for GLS as determined by Intraclass Correlation Coefficient analysis, ICC = 0.81 (0.68–0.89). After multivariate analysis, suPAR was the only biomarker associated with GLS (p = 0.009). suPAR was also associated with diastolic parameters E velocity (p = 0.018), A velocity (p = 0.017), and E/E' ratio (p = 0.033). Interestingly, suPAR was not associated with LVEF (p = 0.916). In addition, suPAR and GLS were found to be age-independent predictors of all-cause mortality, though only GLS remained significant after multivariate adjustment. Conclusions In this cohort of stage IV non-small cell lung cancer patients with normal LVEF and without known heart disease or ESRD, suPAR was associated with GLS and diastolic impairment. suPAR is a readily available inexpensive biomarker; further research is required to evaluate the possible role of suPAR in screening for subclinical LV dysfunction in the high-risk oncological population.